The modern situation and the main directions of fighting and prevention of rabies in the Russian Federation - E. G. Simonova; S. A. Saburova; K. Ju. Levina; A. A. Shabeykin; S. R. Raichich; V. I. Ladnyi (Лечащий Врач)
The purpose of this study is an assessment of modern epizootic-epidemiological features of rabies in the territory of the Russian Federation with the identification of risk factors for complications of the situation for control and surveillance. The study analyzed the results of rabies surveillance in Russia based on data obtained from 2000 to 2017.